Techno-economic Analysis of Rooftop Photovoltaic System (RPVS) using Thin-Frameless Solar Panels for Household Customers in Indonesia: Techno-economic Analysis of Rooftop Photovoltaic System in Indonesia - Rudationo, Carolus Boromeus; Novianto, Bangun; Yandri, Erkata; Susanto, Herry; Setyobudi, Roy Hendroko; Uyun, Aep Saepul; Nur, Syukri Muhammad; Wahono, Satriyo Krido; Widodo, Wahyu; Zekker, Ivar; et al. (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
The availability of thin-frameless solar panels on the market today makes the installation of rooftop Photovoltaic (RPVS) systems more attractive. The purpose of this research is to analyze financially the use of thinframeless solar panels for on-grid RPVS by household electricity customers in Indonesia. The investment cost, the maintenance costs, and the electricity cost savings were involved for the financial analysis, such as Internal Rate of Return (IRR), Net Present Value (NPV), and Pay Back Period (PBP). The calculation is carried out for ideal conditions, the direction of a non-ideal rooftop and the yearly increase of electricity prices is 15 %. The analysis results show that the minimum available rooftop area is still sufficient for the rooftop area needs for solar panel placement, the thin solar panels are safer than standard solar panels, and savings on electricity payments for the return on investment of the RPVS is to be attractive with the IRR > 12 %. The average investment cost of the non-ideal condition is 8 % higher than the ideal condition. This study provides an overview to the policymakers and developers in exploiting the potential of RPVS, especially in Indonesia. For future research directions, this study needs to analyze the technical and economic feasibility of using hybrid smart-grid technology with batteries.